The Aesthetics of Solidarity: Our Lady of Guadalupe and American Democracy - Pineda-Madrid, Nancy ca. 21. Jh. (Horizons, 2022)
"What moves the human heart?" is a question the late Alejandro García-Rivera spent his life examining through his many works on theological aesthetics. In The Aesthetics of Solidarity, Nichole Flores furthers this work by framing her important contribution to the field in a new direction: "What often remains unexamined … is the role the very structures of liberal democracy itself plays in hindering robust participation among Latines and other marginalized groups. Understanding why this is the case invites an exploration of the relationship involving political liberalism, Latine theological aesthetics, Catholic social teaching, and Our Lady of Guadalupe." In this captivating book she advances the overarching claim that "Latine theological aesthetics can help generate a framework for thinking about pluralism and participation within a democracy."